EXAMINING CLINICAL STUDIES ABOUT CUPPING THERAPY IN TURKEY: A SYSTEMATIC REVIEW AND BIBLIOMETRIC ANALYSIS - Yasemin Ucun (International Islamic Medicine Forum, 2024)
There is insufficient quantitative data available on the characteristics of research conducted on cupping therapy. This insufficiency complicates our ability to achieve a more profound understanding of the subject. The primary aim of this work was to assess the outcome of clinical studies outputs in cupping therapy and discuss methodological gaps. Six databases PubMed, Cochrane Library, Medline, TUBITAK ULAKBIM DergiPark, Science Direct, and Google Scholar, were systematically searched from their inception to January 2024. Performance analysis was made in the study. Frequency and distributions were analyzed with SPSS 24. The software Wordclouds software was used to generate visualization. Within the scope of the research, 26 studies that met the selection criteria were accessed. It was determined that the majority of the studies (46.16%) were written in 2019-2021. The most used technique was 3 S (73.07%), and the most preferred point was du 14 point. While the top two variables are oxidative stress and heavy metal levels, the co-word analysis of keywords showed that